Kesulitan Pemahaman Positional Value Numerasi Siswa Fase A pada Sistem Bilangan Desimal - Nur Habibah Rahmawati; Siti Robithoh; Salsabilla, Salsabilla; Khairul Anwar; Fatihul Ihsan Amry (Journal of Humanities, Social Sciences, and Education, 2026)
Low numeracy achievement among Phase A students in the decimal number system remains a serious problem in elementary mathematics learning, particularly regarding difficulties in understanding place value (positional value), marked by high misconceptions in reading, comparing, and performing basic operations on decimal numbers. This study aims to analyze the difficulties in understanding positional value numeracy among Phase A students in the decimal number system. The method used is descriptive literature review by examining 50 relevant scientific sources, including national and international journals, official reports from the Ministry of Education, Culture, Research, and Technology (Kemdikbudristek), and previous research findings on numeracy, decimal numbers, and elementary mathematics learning. The review results indicate that 65-75% of Phase A students experience systematic misconceptions in decimal place value concepts, particularly in the form of whole number bias, decimal comparison errors, and inaccuracies in basic addition and subtraction operations. These difficulties are influenced by the integration of cognitive factors such as whole number interference and overconfidence, social factors like low family numeracy literacy and post-pandemic learning loss impacts, as well as instructional factors involving minimal use of visual media and limited practice time. This study confirms that understanding decimal positional value in Phase A requires a diagnostic, contextual, and locally cultured learning approach through the utilization of manipulatives, ethnopedagogy, and formative assessment.